2020
DOI: 10.1088/1757-899x/862/6/062097
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous pollution by particulate matter of the atmospheric surface layer of the Oktyabrsky district of the city of Krasnoyarsk in 2019

Abstract: Using the air monitoring system of the Krasnoyarsk Scientific Center of the SB RAS, the nature of the atmospheric surface layer pollution by particulate matter (PM2.5) in the Oktyabrsky district of the millionth industrial city was studied. The average annual and seasonal concentrations of PM2.5 were determined in the area where six air monitoring stations are located. Statistical analysis showed that the distribution of PM2.5 in the air is uneven in the Oktyabrsky district of Krasnoyarsk. In the summer air po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previously, it was shown that the pollution of the surface atmosphere with suspended solid particles up to 2.5 μm in size (PM2.5) across the territory of Krasnoyarsk occurs unevenly [7,10]. These studies did not assess the concentration of PM2.5 in the air of the ice-free Yenisei River.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that the pollution of the surface atmosphere with suspended solid particles up to 2.5 μm in size (PM2.5) across the territory of Krasnoyarsk occurs unevenly [7,10]. These studies did not assess the concentration of PM2.5 in the air of the ice-free Yenisei River.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have established that these dependences are statistically significant [4][5][6]. On the scale of cities and megalopolises, the spatial pollution of the surface atmosphere is heterogeneous [7,8]. The uneven distribution of emission sources and the influence of meteorological conditions lead to very different concentrations of air pollutants, including PM, in different areas of the city [9].…”
Section: Introductionmentioning
confidence: 99%